Å forske via internett; Muligheter og utfordringer ved bruk av åpen lenke i rekruttering av informanter og innsamling av data - Sommerseth, Rita; Hanssen, Helene (Nordisk Tidsskrift for Helseforskning, 2012)
Internet-based research; the possibilities and challenges involved in using Open Link for informant recruitment and data collectionSummaryThis article discusses the methodological challenges involved in using the Internet for informant recruitment and data collection in research targeting a specific audience. The article is based on a study focusing on informal carers of people with health and/or social problems. The objectives were to gain knowledge of informal carers’ responsibilities and tasks, burdens and strain, as well as their collaboration with the Health Care Services. Information about the study was disseminated through Facebook and various web sites in autumn 2011, with an Open Link to a questionnaire.  94 women and 14 men participated in the study, 47.3% of whom had a third level education and about 80% had been informal carers for over six years. The majority of respondents were informal carers of people suffering from mental illness, alcohol or drug abuse. Most of the respondents reported that collaboration with the health services was of major importance. The main focus of this article is the possibilities and challenges involved in using Open Link in terms of the sample and credibility of the data.